Quality metrics for emergency abdominal surgery in children: a systematic review. (March 2022) - Sogbodjor, Lisa A.; Singleton, Georgina; Davenport, Mark; Walker, Suellen; Moonesinghe, S. Ramani
Abstract: Background: There is variation in care quality and outcomes for children undergoing emergency abdominal surgery, such as appedectomy. Addressing this requires paediatric-specific quality metrics. The aim of this study was to identify perioperative structure and process measures that are associated with improved outcomes for these children. Methods: We performed a systematic review searching MEDLINE, Embase, CINAHL, Cochrane Library, and Google Scholar for articles published between January 1, 1980 and September 29, 2020 about the perioperative care of children undergoing emergency abdominal surgery. We also conducted secondary searching of references and citations, and we included international professional publications. Results: We identified and analysed 383 peer-reviewed articles and 18 grey literature publications. High-grade evidence pertaining to the perioperative care of this patient group is limited. Most of the evidence available relates to improving diagnostic accuracy using preoperative blood testing, imaging, and clinical decision tools. Processes associated with clinical outcomes include time lapse between time of presentation or initial assessment and surgery, and the use of particular analgesia and antibiotic protocols. Structural factors identified include hospital and surgeon caseload and the use of perioperative care pathways. Conclusions: This review summarises the structural and process measures associated with outcome in paediatric emergency abdominal surgery. Such measures provide a means of evaluating care and identifying areas of practice that require quality improvement, especially in children with appendicitis. Clinical trial registration: PROSPERO CRD42017055285.